Hypernatremia: Correction Rate and Hemodialysis - Saima Nur; Yasir Khan; Saadia Nur; Hassan Boroujerdi (Case Reports in Medicine)
Severe hypernatremia is defined as serum sodium levels above 152 mEq/L, with a mortality rate ≥60%. 85-year-old gentleman was brought to the emergency room with altered level of consciousness after refusing to eat for a week at a skilled nursing facility. On admission patient was nonverbal with stable vital signs and was responsive only to painful stimuli. Laboratory evaluation was significant for serum sodium of 188 mmol/L and water deficit of 12.0 L. Patient was admitted to medicine intensive care unit and after inadequate response to suboptimal fluid repletion, hemodialysis was used to correct hypernatremia. Within the first fourteen hours, sodium concentration only changed 1 mEq/L with a fluid repletion; however, the concentration dropped greater than 20 mEq/L within two hours during hemodialysis. Despite such a drastic drop in sodium concentration, patient did not develop any neurological sequela and was at baseline mental status at the time of discharge.